Borrower Leakage from Costly Screening : Evidence from SME Lending in Peru - Arraiz, Irani; Bruhn, Miriam; Roth, Benjamin N.; Ruiz-Ortega, Claudia; Stucchi, Rodolfo (Elsevier, 2022)
We provide evidence that commercial lenders in Peru suffer leakages in their loan approval process. Leveraging a discontinuity in the loan approval process of a large bank, we find that receiving a loan approval from the bank causes loan applicants to receive offers from other financial institutions as well. Competing lenders captured almost three quarters of the new loans to previously financially excluded borrowers. Importantly, many of these borrowers never took a loan from our partner bank, even after our partner bank approved them. Lenders may therefore underinvest in screening new borrowers and expanding financial inclusion, as their competitors reap some of the benefit. Our results highlight that information spillovers between lenders may operate outside of credit registries.